Deskripsi Kemampuan Penalaran Analogi Siswa Kelas VIII SMP Negeri 2 Gumelar Ditinjau Dari Gender - Surya Anding Permadi (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
This study aims to describe the analytical reasoning ability of Grade VIII students of SMP Negeri 2 Gumelar in terms of gender. The research method used in this research is descriptive qualitative research method. The subjects in this study were students of class VIII D of SMP Negeri 2 Gumelar, totaling 28 students consisting of 15 male students and 13 female students. Sampling was done using purposive sampling technique. In one class, 3 male and 3 female students were selected who had good communication and relatively similar mathematical abilities. Data collection in this study used tests, interviews and documentation. Data analysis techniques used include data reduction, data presentation and conclusion. The validation test used is technical triangulation. The results showed that male students had better analytical reasoning abilities compared to female students. Male students have mastered the four components of analogy reasoning ability encompassing Encoding, Inferring, Mapping and Applying. Meanwhile, female students only mastered the three components of analogy reasoning ability namely Inferring, Mapping and Applying